2021
DOI: 10.1177/02734753211003934
|View full text |Cite
|
Sign up to set email alerts
|

What Works Best: A Systematic Review of Actual Learning in Marketing and Management Education Research

Abstract: After decades of research in marketing and management education, what do we now know about what educational practices work best for improving actual learning? We answer this question with a qualitative systematic literature review of every contribution published in five marketing and management education journals from inception through May 2020 that provides recommendations for evidence-based best pedagogical practice. Contributions were screened to identify empirical studies that employed measures of actual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 109 publications
1
12
0
Order By: Relevance
“…Marketing scholars have explored many excellent pedagogical techniques as shifts in the desired skill set continue (see Cummins et al, 2020; Gray et al, 2012, for reviews of this literature). However, calls for more research into what works in marketing education remain, including calls to study the promising area of client project pedagogy (Bacon & Stewart, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Marketing scholars have explored many excellent pedagogical techniques as shifts in the desired skill set continue (see Cummins et al, 2020; Gray et al, 2012, for reviews of this literature). However, calls for more research into what works in marketing education remain, including calls to study the promising area of client project pedagogy (Bacon & Stewart, 2021).…”
mentioning
confidence: 99%
“…Marketing scholars are prolific in terms of integrating experiential methodologies into the classroom, and live case usage is growing as more business schools seek to improve curriculum relevance and community engagement (Bacon & Stewart, 2021). Many of these scholars have detailed their own experiences using live cases to bolster learning and improve real-world applicability (e.g., Bove & Davies, 2009; Clark et al, 2012; Laukkanen et al, 2013; Lopez & Lee, 2005).…”
mentioning
confidence: 99%
“…A range of motivational theories derived from research such as self-determination theory (SDT) ( Mousa, 2021 ; Tandon et al, 2021 ), expectancy-value theory ( Bacon & Stewart, 2022 ), achievement goal theory ( Senko et al, 2011 ), and control-value theory ( Sholihin et al, 2020 ) have been widely discussed in the business and management education studies during the pandemic to understand the environmental, emotional and psychological factors that motivate students' learning. These theories have been applied to understand the underlying affective, behavioral and cognitive factors which improve learners' motivation, engagement, and learning ( Chiu et al, 2021 ).…”
Section: Results and Findingsmentioning
confidence: 99%
“…Bacon and Stewart (2006) found that most content that students learn in consumer behavior classes is forgotten within 2 years. Elaboration, repeated study, and practice are necessary for longer term retention (Bacon & Stewart, 2022), but such opportunities are usually lacking in programs with many stand-alone courses. Thus, the marketing knowledge taught in college may not help students to be more effective marketers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some sources indicate that the MBA’s marketplace value is the same for the online and face-to-face delivery formats (Driscoll, 2021), and such equivalence would be expected if the education itself was driving the market value. In Bacon and Stewart’s (2022) review of the business education literature, online learning was as effective as face-to-face learning. However, a face-to-face format may create a stronger signal.…”
Section: Literature Reviewmentioning
confidence: 99%